2016
DOI: 10.1016/j.spa.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The sequential empirical process of a random walk in random scenery

Abstract: A random walk in random scenery (Yn) n∈N is given by Yn = ξ Sn for a random walk (Sn) n∈N and iid random variables (ξn) n∈Z . In this paper, we will show the weak convergence of the sequential empirical process, i.e. the centered and rescaled empirical distribution function. The limit process shows a new type of behavior, combining properties of the limit in the independent case (roughness of the paths) and in the long range dependent case (selfsimilarity).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The problem we investigate in the present paper has already been studied in [35] in the case where (S n ) n∈N is a recurrent random walk in Z such that (n − 1 α S n ) n≥1 converges in distribution to a stable distribution of index α, with α ∈ (1,2].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem we investigate in the present paper has already been studied in [35] in the case where (S n ) n∈N is a recurrent random walk in Z such that (n − 1 α S n ) n≥1 converges in distribution to a stable distribution of index α, with α ∈ (1,2].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…is a sequence of independent random variables uniformly distributed on [0, 1] and (Sn)n∈N is a random walk evolving in Z d , independent of the ξ's. In [35], the case where (Sn)n∈N is a recurrent random walk in Z such that (n − 1 α Sn) n≥1 converges in distribution to a stable distribution of index α, with α ∈ (1, 2], has been investigated. Here, we consider the cases where (Sn)n∈N is either :…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally for any arbitrary transient random walk, it can be shown that the sequence { −1/2 , ∈ N} is asymptotically normal (see for instance Spitzer [7] page 53). Among others, we can cite strong approximation results [8][9][10], laws of the iterated logarithm [11][12][13], limit theorems for correlated sceneries or walks [14][15][16][17], large and moderate deviations results [18][19][20][21][22], and ergodic and mixing properties (see the survey [23]). …”
Section: Letmentioning
confidence: 99%